The use of digital-touch screen technology in reminiscence work with people with dementia in Jordanian care homes: a feasibility study - Abdalrahim, Asem Ahmed (2019)
Background: Dementia is progressive degenerative illness is synonymous with cognitive and behavioural decline. Dementia cannot be cured. However, several pharmacological and nonpharmacological approaches can be used to address the symptoms of dementia. Reminiscence therapy (RT) is a non-pharmacological intervention utilising of written, oral, or both accounts of historical events to improve psychological well-being utilising of written, oral, or both accounts of historical events evoke the long-term memories of the people with dementia (PwD), and improve psychological well-being. Using digital-touch screen technology to deliver RT content is new in the care home activities. The digital RT application contains a wide range of stimuli to prompt reminiscence amongst PwD in the care homes. This is the first study to evaluate the feasibility and acceptability of using digital-touch screen technology to deliver RT for PwD in Jordanian care homes.